An exploratory analysis of the effects of ownership change on airport competition - Pagliari, Romano; Graham, Anne B. (Elsevier, 2019)
Common or group ownership of airports poses a particular challenge for policy-makers, in that consumers (airlines and passengers) may not have access to benefits that stem from a more competitive system (e.g. lower prices, higher quality of service). However, whilst the arguments for and against group versus individual operations are well known, there are only limited practical cases when a change from common to individual ownership has occurred. One such case is in Scotland where the ownership of Edinburgh and Glasgow airports was separated in 2012. Therefore, the aim of this paper is to undertake a comparative assessment of the impact of this ownership change on the nature of competition between the two airports for the period 2006–2017. Catchment areas overlap, so it was hypothesised that separate ownership would lead to a more intense competitive rivalry with consequent effects on route development, traffic growth, the level/structure of aeronautical charges, financial performance, capital investment and quality of service. A number of key performance indicators covering these areas have been analysed, both before and after 2012 to assess whether there is evidence of a more competitive environment. The main findings are (i) traffic and routes have increased at both airports, although their relative roles appear to have changed; (ii) published charge levels have increased (iii) aeronautical yield has increased at Edinburgh but declined at Glasgow; (iv) prices have diverged reflecting differences in core market price elasticities; strategies have also been driven by a broader financial imperative around maximising EBITDA given declining unit costs and stagnation in non-aeronautical yields; (vi) certain performance indicators suggest that efficiency and service quality have improved. The implications for policy-makers are that airport market re-structuring and ownership change will most likely lead to divergence in pricing and route development strategies.
Keywords: Aeronautical charges; Airport ownership change; Divestment; Airport route development; Airport competition; Airport financial performance